Impact of Different Serum Potassium Levels on Postresuscitation Heart Function and Hemodynamics in Patients with Nontraumatic Out-of-Hospital Cardiac Arrest - Yan-Ren Lin; Yuan-Jhen Syue; Tsung-Han Lee; Chu-Chung Chou; Chin-Fu Chang; Chao-Jui Li (Bioinorganic Chemistry and Applications)
Background. Sustained return of spontaneous circulation (ROSC) can be initially established in patients with out-of-hospital cardiac arrest (OHCA); however, the early postresuscitation hemodynamics can still be impaired by high levels of serum potassium (hyperkalemia). The impact of different potassium levels on early postresuscitation heart function has remained unclear. We aim to analyze the relationship between different levels of serum potassium and postresuscitation heart function during the early postresuscitation period (the first hour after achieving sustained ROSC). Methods. Information on 479 nontraumatic OHCA patients with sustained ROSC was retrospectively obtained. Measures of early postresuscitation heart function (rate, blood pressure, and rhythm), hemodynamics (urine output and blood pH), and the duration of survival were analyzed in the case of different serum potassium levels (low: <3.5; normal: 3.5–5; high: >5 mmol/L). Results. Most patients (59.9%, n = 287) had previously presented with high levels of potassium. Bradycardia, nonsinus rhythm, urine output <1 ml/kg/hr, and acidosis (pH < 7.35) were more common in patients with high levels of potassium (all p<0.05). Compared with hyperkalemia, a normal potassium level was more likely to be associated with a normal heart rate (OR: 2.97, 95% CI: 1.74–5.08) and sinus rhythm (OR: 2.28, 95% CI: 1.45–3.58). A low level of potassium was more likely to be associated with tachycardia (OR: 3.54, 95% CI: 1.32–9.51), urine output >1 ml/kg/hr (OR: 5.35, 95% CI: 2.58–11.10), and nonacidosis (blood pH >7.35, OR: 7.74, 95% CI: 3.78–15.58). The duration of survival was shorter in patients with hyperkalemia than that in patients whose potassium levels were low or normal (p<0.05). Conclusion. Early postresuscitation heart function and hemodynamics were associated with the serum potassium level. A high potassium level was more likely to be associated with bradycardia, nonsinus rhythm, urine output <1 ml/kg/hr, and acidosis. More importantly, a high potassium level decreased the duration of survival.